2011
DOI: 10.2971/jeos.2011.11053
|View full text |Cite
|
Sign up to set email alerts
|

Contrast transfer characteristics of the light sword optical element designed for presbyopia compensations

Abstract: The paper discusses the abilities of the light sword optical element (LSOE) for presbyopia compensation. The imaging properties are analyzed by means of the modulation transfer functions and output images of the star resolution test. All numerical calculations are performed assuming an optical setup simulating the presbyopic human eye with 3 mm pupil acting on-axis and based on the Gullstrand model. In order to have a meaningful comparison we expand our study and present adequate analysis for other elements po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…23 The optical properties of the LSL and its imaging with extended depth of field have been widely studied numerically and experimentally. [20][21][22][23][24]26,27 These investigations confirmed that the images formed by the LSL have acceptable resolution and contrast. Therefore, lenses with angular modulation of optical power such as the LSL can be useful for imaging with extended depth of field.…”
supporting
confidence: 64%
“…23 The optical properties of the LSL and its imaging with extended depth of field have been widely studied numerically and experimentally. [20][21][22][23][24]26,27 These investigations confirmed that the images formed by the LSL have acceptable resolution and contrast. Therefore, lenses with angular modulation of optical power such as the LSL can be useful for imaging with extended depth of field.…”
supporting
confidence: 64%
“…According to previously reported theoretical studies, numerical simulations, and qualitative experiments [12][13][14][15][16][17][18], an element of this kind can form recognizable images of acceptable quality in the presence of a defocus of 0-4 diopters. The LSL demonstrated its superiority over other solutions designed especially for multifocal and EDF imaging.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to briefly mention the tilt and decentration of the element, and the influence of the LSL junction on vision comfort. According to [17], the MTFs illustrating imaging realized by the LSL have nonzero values for wide ranges of frequencies and do not exhibit substantial oscillations. On the other hand, for defocusing values close to 0 diopter, these MTFs have small values for a large range of spatial frequencies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations